Help or Hindrance? The Impact of Harmonised Standards on African Exports - Czubala, Witold; Shepherd, Ben; Wilson, John S. (2012)
We test the hypothesis that product standards harmonised to de facto international standards are less trade restrictive than ones that are not. To do this, we construct a new database of European Union (EU) product standards. We identify standards that are aligned with International Organisation for Standardisation (ISO) standards (as a proxy for de facto international norms). We use a sample-selection gravity model to examine the impact of EU standards on African textiles and clothing exports, a sector of particular development interest. We find robust evidence that non-harmonised standards reduce African exports of these products. EU standards which are harmonised to ISO standards are less trade restricting. Our results suggest that efforts to promote African exports of manufactures may need to be complemented by measures to reduce the cost impacts of product standards, including international harmonisation. In addition, efforts to harmonise national standards with international norms, including those through the World Trade Organisation Technical Barriers to Trade Agreement, promise concrete benefits through trade expansion.